The je-ne-sais-quoi - Scholar, R; Scholar, Richard (2003)
The purpose of this thesis is to analyse the je-ne-sais-quoi through its history and its pre-history. When we are moved by something we cannot identify, but whose effects we cannot fail to recognize, how should we try and come to terms with our experience? The je-ne-sais-quoi rises to prominence as a keyword in such discussions during the period studied. This thesis offers the first full-length study of the word and its significance to literary and philosophical writing of that period. It traces its precursors, its rise as a noun in mid-seventeenth-century France and England, and its fall from grace. Previous historical work has generally restricted the word's application to aesthetics; this study examines its significance in the philosophy of nature and the passions as well as culture. It combines historical method and philosophical enquiry to inform the close analysis of examples. The aim is to consider what the je-ne-sais-quoi is and how it finds expression in writing. A fourfold thesis is proposed, (i) The lexical je-ne-sais-quoi, in its core meaning, refers to an inexplicable force with sudden and vital effects, (ii) This force remains ever on the move by unsettling sedimented words, passing through current ones, and abandoning these as they too undergo sedimentation, (iii) The word history of the je-ne-sais-quoi,/em> encapsulates this movement. The term is first used to unsettle its semantic precursors (by Descartes and others), becomes current in writing of the mid-seventeenth century (that of Corneille and Pascal in particular), but soon settles into the sediment of polite culture (as Méré, Bouhours, and English Restoration comedy show), (iv) Returning the word to the mobile non-substantival forms of its pre-history in Montaigne, to whom a chapter-length study is devoted, uncovers a form of writing that captures the force of the je-ne-sais-quoi better than the settled word itself. The task of literature is to lend form to the je-ne-sais-quoi by naming it in its inexplicable reality and by describing how it falls, like a disaster, into our experience.